THE EFFECT OF CAPITAL ADEQUACY RATIO, NON-PERFORMING FINANCING, BANK SIZE AND FINANCING TO DEPOSIT RATIO ON SHARIA BANKS PERFORMANCE IN INDONESIA - Novaldi Yudistira; Ristati Ristati (PT. Radja Intercontinental Publishing, 2022)
The purpose of this study is to examine the effect of the capital adequacy ratio, non-performing financing, bank size and financing to deposit ratio on financial performance of Islamic banks in Indonesia. The data used in this study are capital adequacy ratios, non-performing financing, bank size, financing to deposit ratio and financial performance of Islamic banks in Indonesia for 2013-2020. The data is accessed through the website www.ojk.go.id Data analysis method in this study is panel data regression analysis method. The results of the study find that capital adequacy ratio has positive and significant effect on financial performance, while non-performing financing has negative and significant effect on financial performance. Bank size and financing to deposit ratio have no significant effect on financial performance.